Measuring the intensive care experience: A cross‐sectional survey of patient and family experiences of critical care. Issue 23 (6th June 2021) - Williams, Helen; Gow, Jeff; Rana, Rezwanul; Rouse, Alan; Chinthamuneedi, Meher; Beccaria, Gavin; Ralph, Nicholas
Abstract: Aims and Objectives: To report patient and family intensive care experiences using the M easuring the I ntensive C are E xperience (MICE) tool across two intensive care units (ICU). Background: The patient and family experience of care is an important indicator for quality improvement of ICUs, yet few studies evaluate both patient and family experiences in relation to overall care quality as well as specifically measuring quality of medical care, nursing care and organisational care as well as overall experience of the quality of intensive care. Design: A cross‐sectional survey. Methods: A 23 item survey was administered to ICU patients and their family members across two ICUs, a regional 189‐bed hospital and a metropolitan 227‐bed hospital in Queensland, Australia. The response rate was 272 of 394 ICU patients (36.4%). STROBE guidelines were used in reporting this study. Results: Findings indicate a highly positive overall experience of ICU care among patients and families. However, patients reported areas of unmet needs following their stay in ICU broadly related to (1) symptom management, education and information support, and (2) improving the incorporation of patient and family care ICU‐related shared decision‐making. Conclusions: Supportive interventions are needed that target improve symptom management and inform and education ICU patients. Relevance to clinical practice: The MICE survey facilitated the identification of a range of areas requiring quality improvement. Improving the integration of patients and families into shared decision‐making and support is a key aspect for quality improvement.